2021
DOI: 10.2147/ott.s322697
|View full text |Cite
|
Sign up to set email alerts
|

TFF-1 Functions to Suppress Multiple Phenotypes Associated with Lung Cancer Progression

Abstract: Introduction Trefoil Factor (TFF) is a member of a protein family comprised of three isoforms, of which TFF-1 exhibits antithetical functions; promotion or suppression of cell proliferation, survival and invasion, depending on the cancer type. However, the pathobiological function of TFF-1 in lung carcinoma has been still unclear. Methods We examined the expression and secretion of TFF-1 using cultured human lung carcinoma cells by immunoblotting, immunofluorescence, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In cancer cell lines, exogenous TFF1 consistently reduced cell proliferation by delaying the G1 to S phase transition in human colonic and gastric carcinoma cells (29). Similarly, in a previous study, it was shown that TFF1 can suppress cell proliferation, survival, migration and invasion in lung carcinoma cells (30). Notably, the expression of TFF1 is also predictive of improved survival time for patients with breast cancer (27,31).…”
Section: Diagnostic Utility Of Trefoil Factor Families For the Early ...mentioning
confidence: 55%
“…In cancer cell lines, exogenous TFF1 consistently reduced cell proliferation by delaying the G1 to S phase transition in human colonic and gastric carcinoma cells (29). Similarly, in a previous study, it was shown that TFF1 can suppress cell proliferation, survival, migration and invasion in lung carcinoma cells (30). Notably, the expression of TFF1 is also predictive of improved survival time for patients with breast cancer (27,31).…”
Section: Diagnostic Utility Of Trefoil Factor Families For the Early ...mentioning
confidence: 55%
“…3b ). Immunofluorescence experiments demonstrated that N protein (in green) was expressed and co-localized with the lung epithelial cell marker TFF-1 43 (in blue) in the lung organoids infected with Lentivirus-N (Supplementary Fig. 3c ).…”
Section: Resultsmentioning
confidence: 99%